Building Partnerships and Bridging Science and Policy to Address the Biological Invasions Crisis. (13th February 2019) - Barney, Jacob N.; Schenk, Todd; Haak, David C.; Salom, Scott; Brown, Bryan; Hotchkiss, Erin R.
Abstract: Biological invasions are one of the grand challenges facing society, as exotic species introductions continue to rise and can result in dramatic changes to native ecosystems and economies. The scale of the "biological invasions crisis" spans from hyperlocal to international, involving a myriad of actors focused on mitigating and preventing biological invasions. However, the level of engagement among stakeholders and opportunities to collaboratively solve invasives issues in transdisciplinary ways is poorly understood. The Biological Invasions: Confronting a Crisis workshop engaged a broad group of actors working on various aspects of biological invasions in Virginia, USA—researchers, Extension personnel, educators, local, state, and federal agencies, nongovernmental organizations, and land managers—to discuss their respective roles and how they interact with other groups. Through a series of activities, it became clear that despite shared goals, most groups are not engaging with one another, and that enhanced communication and collaboration among groups is key to designing effective solutions. There is strong support for a multistakeholder coalition to affect change in policy, public education/engagement, and solution design. Confronting the biological invasions crisis will increasingly require engagement among stakeholders.